2015
DOI: 10.1007/s11105-015-0875-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of EST-SSR Markers in Taxodium ‘zhongshansa’

Abstract: Taxodium 'zhongshansa', an extremely floodtolerant tree species, has been widely planted in eastern China due to its environmental attributes. Although much progress has been made in understanding its physiological response to flooding stress, as well as its rapid propagation and variety selection, little is known regarding its molecular genetics due primarily to a lack of reliable molecular markers. In this paper, 108,692 expressed sequence tags (ESTs) with a total size of 69.3 Mb derived from T. 'zhongshansa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…Characterization of SSR analysis revealed that, the monoucleotide repeats were most abundant 411,156 (94.7%) in papaya floral unigenes which is similar to previous reports on several plant species namely pea [47], olive [48], Camellia sinensis [49], tobacco [50] and Taxodium zhong shansa [51], but in contrast to those from pineapple [52], forage legume [53] in which di-and tri-nucleotides were identified as the most abundant repeats. The frequency of mononucleotide was found to be highest (94.7%) as compared to other repeat types in our study which is similar to previous report of papaya in which mononucleotides contributed maximum (69.1%) [40].…”
Section: Types Of Motifs American Journal Of Plant Sciencessupporting
confidence: 86%
“…Characterization of SSR analysis revealed that, the monoucleotide repeats were most abundant 411,156 (94.7%) in papaya floral unigenes which is similar to previous reports on several plant species namely pea [47], olive [48], Camellia sinensis [49], tobacco [50] and Taxodium zhong shansa [51], but in contrast to those from pineapple [52], forage legume [53] in which di-and tri-nucleotides were identified as the most abundant repeats. The frequency of mononucleotide was found to be highest (94.7%) as compared to other repeat types in our study which is similar to previous report of papaya in which mononucleotides contributed maximum (69.1%) [40].…”
Section: Types Of Motifs American Journal Of Plant Sciencessupporting
confidence: 86%
“…We used 100 primer pairs, selected randomly from a multitude of primer pairs identified via transcriptome analysis, to evaluate the quality and effectiveness of the new EST-SSR markers. Seventy-two primer pairs (72%) generated clear bands from L. formosana genomic DNA; the amplification rate was significantly higher than that of the SSR markers of the transcriptomes of Robinia (25%) [48] and Taxodium 'zhongshansa' (51.1%) [49]. Eighteen primer pairs did not yield amplicons, despite adjustment for annealing temperature.…”
Section: Discussionmentioning
confidence: 95%
“…[19], Dipteronia spp . [20], Taxodium ‘zhongshansa’ [21], E . ulmoides [12], Pinus koraiensis [22], and Cunninghamia lanceolata [23]; however, to date, they have not been reported in S .…”
Section: Introductionmentioning
confidence: 99%